Analysis of the transistor efficiency of gas phase Zn diffusion In0.53Ga0.47As nTFETs at different temperatures - Bordallo, C.; Martino, J. A.; Agopian, P. G.D. [UNESP]; Alian, A.; Mols, Y.; Rooyackers, R.; Vandooren, A.; Verhulst, A. S.; Simoen, E.; Claeys, C.; Collaert, N. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
In this work, the influence of the temperature and the different equivalent oxide thickness (EOT) of In0.53Ga0.47As nTFETs fabricated with gas phase Zn diffusion is analyzed. The different devices have in their gates stacks 3 nm of HfO2 (with an EOT of 1 nm) or 2 nm of HfO2 (with an EOT of 0.8 nm). The use of an EOT of 0.8 nm increases the band-to-band tunneling generation and also improves the subthreshold region characteristics, presenting a sub 60 mV/dec minimum subthreshold swing (56 mV/dec) at room temperature, resulting in better efficiency in weak conduction. Considering the temperature influence, the on-state current is less affected than the off-state current due to the band-to-band tunneling mechanism. In the subthreshold region the temperature decrease, which strongly reduces the off-state current, allows the band-to-band tunneling current to be more dominant, resulting in a better subthreshold swing and, consequently, a better transistor efficiency in the weak conduction regime. The opposite behavior occurs when heating the devices, reducing the influence of the band-to-band tunneling in the subthreshold region, degrading both the subthreshold swing and transistor efficiency in the weak conduction regime. In the strong conduction regime, the transistor follows the transconductance tendency, increasing for higher temperatures.
Keywords: Analog Parameters; III-V materials; TFET; Transistor efficiency